Learning statistics using infographics: A powerful tool to engage communication students in learning activities - Silvestre, Cláudia (2021)
We live in an information-driven society, where statistics play an important role. So, it is very important to promote statistical literacy, since they are not just consumers but also producers of statistical news. That is a big challenge due to the fact that our communication students do not have a great interest in statistics. To engage our students and motivate them to learn, we use infographics which are a visual tool to help understanding a concept or data set, and communicating it clearly and effectively by using visual elements. Our experience reveals that analysing and creating infographics based on real data, can be a powerful motivator for students to learn and improve their statistical skills.